Customized Cochlear Implant Positioning in a Patient With a Low- Grade Glioma: Towards the Best MRI Artifact Management. Issue 6 (17th July 2022) - Canzi, Pietro; Luzzi, Sabino; Carlotto, Elena; Simoncelli, Anna; Brondino, Natascia; Marconi, Stefania; Magnetto, Marianna; Lucifero, Giotta A.; Avato, Irene; Manfrin, Marco; Auricchio, Ferdinando; Preda, Lorenzo; et al.
Abstract : Objective: To report the personalized decision-making pro- cess adopted for a cochlear implant (CI) candidate requiring magnetic resonance imaging (MRI) brain surveillance. Study Design: Clinical capsule report. Setting: Tertiary academic referral center. Patient: A 23-year-old man affected by posttraumatic bilat- eral profound hearing loss, already in radiological follow-up for a suspected small left cuneal low-grade glioma. Interventions: A multidisciplinary approach involving preoperative MRI simulations and 3D printed (3DP) models aiming to adapt the CI position to facilitate MRI brain lesion visibility. Main Outcome Measures: MRI visibility and surgical approach. Results: Preoperative MRI scans with the placement of an Ultra 3D CI were performed simulating different implant location to assess the brain lesion visibility in MRI. CI was positioned 9 cm away from the external auditory canal with an angle of 90 degrees. To assess the technical feasibility of the surgical procedure, a patient-specific 3DP head model was produced preoperatively. The postoperative course was uneventful, the patient showed a significant benefit from CI, and the brain lesion was highly visible at the MRI follow-up. Conclusions: The employment of strategies aimed at improving the MRI quality in CI recipients still represents a topic requiring attention. Thanks to multidisciplinary team collaboration, in our case, the CI position was successfully determined to allow unhindered MRI visibility of a specific intracranial structure.